EFL Cambridge Curriculum Implementation at Kharisma Bangsa Middle School: Teachers' Perspective - Ameliya, Megita; Izzah, Lidiyatul; Aguirre, Angel IIlaw (English Language in Focus (ELIF), 2024)
This study investigates the implementation of the Cambridge Curriculum at Kharisma Bangsa Secondary School and its impact on teaching English as a Foreign Language (EFL). Data were collected using a qualitative case study approach, which included interviews, observations, and document analysis. Miles, Huberman, and Saldana's models were used in the analysis, with emphasis on the systematic phases of data collection, condensation, analysis, and aggregation. The purpose of this study is to assess the effectiveness of the Cambridge Curriculum in meeting learning objectives and improving the quality of EFL education. It investigates a variety of topics, including curriculum implementation strategies, supporting and challenging factors encountered, and the curriculum's overall outcomes in the Indonesian educational context. The primary results indicate that the Cambridge Curriculum has significantly influenced the teaching methodologies and assessments.